Xylo-Oligosaccharides, Preparation and Application to Human and Animal Health: A Review - Chen, Yuxia; Xie, Yining; Ajuwon, Kolapo M.; Zhong, Ruqing; Li, Tao; Chen, Liang; Zhang, Hongfu; Beckers, Yves; Everaert, Nadia (Frontiers in Nutrition, 2021)
Xylo-oligosaccharides (XOS) are the degraded products of xylan prepared via chemical, physical or enzymatic degradation. XOS not only exhibit some specific physicochemical properties such as excellent water solubility and high temperature resistance, but also have a variety of functional biological activities including anti-inflammation, antioxidative, antitumor, antimicrobial properties and so on. XOS have been demonstrated to reduce the occurrence of human health-related diseases, improve the growth and resistance to diseases of animals. Therefore, XOS have potential for extensive application for promoting human and animal health. This review aims to summarize the preparation methods of XOS, and will also discuss the current application of XOS to human and animal health.